Study on Triopoly Dynamic Game Model Based on Different Demand Forecast Methods in the Market. (6th July 2017) - Ma, Junhai; Sun, Lijian; Zhan, Xueli
Abstract : The impact of inaccurate demand beliefs on dynamics of a Triopoly game is studied. We suppose that all the players make their own estimations on possible demand with errors. A dynamic Triopoly game with such demand belief is set up. Based on this model, existence and local stable region of the equilibriums are investigated by 3D stable regions of Nash equilibrium point. The complex dynamics, such as bifurcation scenarios and route to chaos, are displayed in 2D bifurcation diagrams, in which e 1 and α are negatively related to each other. Basins of attraction are investigated and we found that the attraction domain becomes smaller with the increase in price modification speed, which indicates that all the players' output must be kept within a certain range so as to keep the system stable. Feedback control method is used to keep the system at an equilibrium state.